Subchronic Toxicity of Microcystin-LR on Young Frogs (Xenopus laevis) and Their Gut Microbiota - Li, Jinjin; Sun, Hongzhao; Wang, Chun; Li, Shangchun; Cai, Yunfei (Frontiers in Microbiology, 2022)
Although toxic effects of microcystins (MCs) in mammals and fish have been extensively studied, the effects of MCs on the immune system and gut microbiota of amphibians have not received sufficient attention. As MCs cause general damage to the vertebrate liver and immune system and trigger an inflammatory response, and the gut microbiota is closely related to host metabolism and immunity, we speculated that MCs can cause changes in the immune system and gut microbiota of amphibians. To verify this, we examined the intestinal and liver injury of Xenopus laevis exposed to different microcystin-leucine-arginine (MC-LR) concentrations and the effects on the gut microbiota through high-throughput sequencing of 16S rDNA of the gut microbiota combined with histopathological analysis, enzyme activity determination, and qRT-PCR. Our results showed that MC-LR caused focal infiltration of inflammatory cells and increased the number of T cells and local congestion and vacuolization in X. laevis liver, but reduced the number, density, height, and regularity of villi. These liver and intestinal injuries became more obvious with an increase in MC-LR concentration. MC-LR significantly decreased the activities of malondialdehyde and alkaline phosphatase and the expression of TGF-β in the liver. Moreover, MC-LR significantly altered the gut microbiota of X. laevis. The relative abundance of Firmicutes and Bacteroidetes in high-concentration MC-LR groups was significantly reduced compared to that in low-concentration MC-LR groups, whereas Fusobacteria was significantly enriched. The metabolic gene composition of the gut microbiota in low-concentration MC-LR (≤5 μg/L) groups was significantly different from that in high-concentration MC-LR (≥20 μg/L) groups. These results deepen our understanding of the toxicity of MCs to aquatic organisms and assessment of the ecological risk of MCs in amphibians.